Impact of COVID-19 Packages on MSME Financing in India - Silu Muduli (ZBW - Leibniz Information Centre for Economics, 2022)
The small, micro, and medium enterprise (MSME) sector in India was severely affected during the COVID-19 pandemic. The Government of India and the Reserve Bank of India brought numerous policy measures to revive and provide external liquidity support to borrowers in the MSMEs sector. Credit growth picked up in the MSME sector following the introduction of the Emergency Credit Line Guarantee Scheme (ECLGS) scheme in May 2020, particularly of a loan of size less than 10 lakh. Initially, it benefited borrowers already having a relationship with the bank, later the benefit passed to new borrowers. On the usage of funds, nearly 45 per cent of these loans were used for clearing dues of vendors and 29 per cent to restart the business. On the performance of ECLGS loans, 88 per cent of loans are standard assets and 1.96 per cent are non-performing assets as of March 31, 2021.
Keywords: G28; G32; H12; 330; COVID-19; MSMEs Relief packages; MSME financing